Molecular analysis of the VP7 gene of pheasant rotaviruses identifies a new genotype, designated G23 - Ursu, Krisztina; Kisfali, Péter; Rigó, Dóra; Ivanics, Éva; Erdélyi, Károly; Dán, Ádám; Melegh, Béla; Martella, Vito; Bányai, Krisztián (Archives of virology, 2009)
Rotavirus-associated enteritis has been reported in pheasants, but there is no information on the genetic/antigenic features of pheasant rotaviruses. In this study, we sequenced the VP7-encoding genome segment of three pheasant rotavirus strains detected during 2008 in Hungary. The full-length genome segment was 1,070 bp long, while the open reading frame was predicted to encode a 330-aa-long protein. The nucleotide sequence identities among the three pheasant rotavirus strains were high (≥94%), whereas the range of nucleotide sequence identities to other avian and mammalian rotavirus VP7 genes fell between 68 and 73% and between 60 and 66%, respectively. Our findings indicate that these Hungarian pheasant rotaviruses need to be considered representatives of a new VP7 genotype specificity, designated G23.